1986
DOI: 10.1254/jjp.42.453
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Substance P on Glycoprotein Secretion from Acinar Cells of the Rat Submandibular Gland

Abstract: Abstract-The action of substance P on glycoprotein secretion from acinar cells of the rat submandibular gland was described in this report. Salivation elicited by i.v. injection of 0.5 to 20 ug/kg of substance P was increased dose-dependently, and its flow rate was highest at the first 1 min. Major glycoprotein species secreted into saliva by substance P-stimulus were shown to be electrophoretically identical with those found in acini, but not granular convoluted tubules. These results support the view that su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…We found that characteristic glycoproteins in the acini are secreted into the saliva after stimulation by the non-specific 1 -adrenergic agent isoproterenol (15), as well as after stimulation by the cholinergic agent pilocar pine (16) and by substance P (17), whereas glycoproteins characteristic of the granular convoluted tubules are secreted in response to the a,-adrenergic agent, methoxamine (18,19).…”
mentioning
confidence: 90%
“…We found that characteristic glycoproteins in the acini are secreted into the saliva after stimulation by the non-specific 1 -adrenergic agent isoproterenol (15), as well as after stimulation by the cholinergic agent pilocar pine (16) and by substance P (17), whereas glycoproteins characteristic of the granular convoluted tubules are secreted in response to the a,-adrenergic agent, methoxamine (18,19).…”
mentioning
confidence: 90%